2020
DOI: 10.1039/d0ra01117g
|View full text |Cite
|
Sign up to set email alerts
|

Superior antitumor effect of self-assembly supramolecular paclitaxel nanoparticles

Abstract: Carrier-free paclitaxel nanoparticles with higher drug loading efficiency, less non-specific toxicity and more stable and durable antitumor effect of Ptx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…MDR-related HCT 15 cells overexpressing p-gp were incubated in a cell culture medium containing RPMI-1640 medium, 10% FBS, and 1% AA at 37 °C in a humidified 5% CO 2 atmosphere. The anticancer efficacy of PTX itself and that of PTX@TNPs with different drug loads were evaluated using the CCK-8 assay kit as previously described [ 29 , 30 ]. HCT 15 cells were seeded onto 96-well plates at a density of 10,000 viable cells per well and cultured overnight at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…MDR-related HCT 15 cells overexpressing p-gp were incubated in a cell culture medium containing RPMI-1640 medium, 10% FBS, and 1% AA at 37 °C in a humidified 5% CO 2 atmosphere. The anticancer efficacy of PTX itself and that of PTX@TNPs with different drug loads were evaluated using the CCK-8 assay kit as previously described [ 29 , 30 ]. HCT 15 cells were seeded onto 96-well plates at a density of 10,000 viable cells per well and cultured overnight at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…e particles were observed by transmission electron microscope as spherical objects of uniform size, and the diameter size was consistent with the particle size detection results. Experimentally, the drug content of paclitaxel nanoparticles was 19.58%, and the embedding rate was 93.25% [19].…”
Section: Analysis Of Paclitaxel Nanoparticles In Thementioning
confidence: 99%
“…In vitro studies demonstrated that PTX loaded in PEG-based micelles exhibited enhanced tumor inhibitory comparing to free PTX alone (with IC 50 values of PTX-NPs and free PTX were 123.9 × 10 −9 and 204.6 × 10 −9 m, respectively). [163] Mutlu-Agardan et al used 3,3′-dithiodipropionic acid to introduce disulfide bond between PTX and PEG 2000 , introducing glutathione-responsive cleavage (Figure 7a). [164] On such reduction-sensitive drug delivery vehicle, Shi et al further introduced RGD peptide which targets 𝛼 v 𝛽3 integrin that is highly expressed by cancer cells.…”
Section: Poly(ethylene Glycol)mentioning
confidence: 99%